PENERAPAN PEMBELAJARAN CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA S1 PGMIPA- UNGGULAN - Sakur '; Nahor Murani Hutapea (Jurnal Pendidikan, 2014)
The purpose of the research was to determine the increase theAbility of Mathematical Problem Solving (KPMM) students through theapplication of Creative Problem Solving (CPS) in learning mathematics andimprove the quality of lectures a course of Mathematics Senior High School. Ifthe application of learning CPS executed properly, it can improve studentsKPMM and improve the quality of lectures a course of Mathematics Senior HighSchool. Analysis of data on activities lecture and students showed that thestudents work together to solve the problems posed in Works Sheet has beenperforming well. Improved learning outcomes can be seen from the developmentof the average value of students of each cycle and the percentage of students thatis value well. The results of the data analysis showed that the application oflearning CPS that executed properly can improve students KPMM and increasethe percentage of students that is value well.Keywords: Creative Problem Solving, Mathematical Problem Solving Ability